ANTI-SARS-COV-2 ANTIBODIES IN MACEDONIAN HEALTHCARE WORKERS: AN INTERIM ANALYSIS - Tosheska Trajkovska Katerina; Babacic Haris; Toseska-Spasova Natasa; Kostovska Irena; Bogdanska Jasna; Labudovikj Danica; Svetlana Cekovska; Brezovska Julijana; Ampova, Hristina; Emin, Melda; Stanojevska-Petrusevska Elena; Topuzovska Sonja (Faculty of Medicine, University Ss. Cyril and Methodius in Skopje, 2021)
Introduction. The spectrum of COVID-19 in adults ranges from asymptomatic infection to mild respiratory tract symptoms to severe pneumonia with acute respiratory distress syndrome (ARDS) and multiorgan dysfunction. Healthcare workers (HCWs) are exposed to the virus at a greater extent than society as a whole and may be considered at an elevated risk of infection. The aim of the study was to estimate the seroprevalence of SARS-CoV-2 antibodies among HCWs all over the territory of North Macedonia. Material and methods. In this interim analysis, we included 2,334 healthcare workers (HCW), who were tested for serum IgM and IgG antibodies to SARS-CoV-2 virus during the period from 28/05/2020 to 20/08/2020. Chemiluminescent (CLIA) analytical system was used for detection of anti SARS CoV-2 IgM and IgG antibodies. Results. A total of 195 HCWs, out of 2,334, tested positive for either IgM or IgG anti-SARS-CoV-2 serum antibodies (IgM/G+). Of these, 167 individuals tested positive for IgM antibodies (IgM+) and 54 tested positive for IgG antibodies (IgG+). Based on these data, the cumulative incidence of anti-SARS-CoV-2 antibodies in HCWs during the period from 28/05/2020 to 20/08/2020 was estimated at 8.355% (95% CI = 7.279-9.57%). Conclusions. HCWs represent a population at high risk of contracting COVID-19. To decrease the risk of SARS-CoV-2 infection, absolute adherence to infection preventive measures is needed: proper use of face masks at all times in the workplace, avoiding of overcrowding in different working spaces, and keeping a recommended distance in meetings, clinical handouts and work meals. Early identification and isolation of infected HCWs is highly recommended.
Keywords: SARS-CoV-2; COVID-19; healthcare workers; IgM; IgG antibodies